2022
DOI: 10.3390/antiox11071294
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Advances the Genetic Diagnosis of Cerebral Cavernous Malformation (CCM)

Abstract: Cerebral Cavernous Malformation (CCM) is a cerebrovascular disease of genetic origin that predisposes to seizures, focal neurological deficits and fatal intracerebral hemorrhage. It may occur sporadically or in familial forms, segregating as an autosomal dominant condition with incomplete penetrance and highly variable expressivity. Its pathogenesis has been associated with loss-of-function mutations in three genes, namely KRIT1 (CCM1), CCM2 and PDCD10 (CCM3), which are implicated in defense mechanisms against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Moreover, additional sources of oxy-inflammatory events already implicated in CCM disease pathogenesis are pathogen-associated molecular patterns (PAMPs), including bacterial PAMPs known to activate TLR4 signaling, such as lipopolysaccharide (LPS) [ 69 ], as well as hypoxia [ 70 ]. Furthermore, consistent with the fact that focal oxy-inflammatory conditions contribute significantly to CCM lesion formation and severity, distinct genetic modifiers of oxy-inflammatory responses have been identified as linked to the incomplete penetrance and highly variable expressivity of CCM disease in large cohorts of fCCM cases [ 8 , 44 , 46 , 51 ]. In addition, new intriguing and significant evidence in animal models suggests that CCM gene mutations can have pathological effects not limited to CCM disease, as they may predispose to the development of other pathological conditions associated with abnormal oxy-inflammatory responses, such as atherosclerosis and hepatic metabolic, antioxidant, and antiglycative dysfunctions [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, additional sources of oxy-inflammatory events already implicated in CCM disease pathogenesis are pathogen-associated molecular patterns (PAMPs), including bacterial PAMPs known to activate TLR4 signaling, such as lipopolysaccharide (LPS) [ 69 ], as well as hypoxia [ 70 ]. Furthermore, consistent with the fact that focal oxy-inflammatory conditions contribute significantly to CCM lesion formation and severity, distinct genetic modifiers of oxy-inflammatory responses have been identified as linked to the incomplete penetrance and highly variable expressivity of CCM disease in large cohorts of fCCM cases [ 8 , 44 , 46 , 51 ]. In addition, new intriguing and significant evidence in animal models suggests that CCM gene mutations can have pathological effects not limited to CCM disease, as they may predispose to the development of other pathological conditions associated with abnormal oxy-inflammatory responses, such as atherosclerosis and hepatic metabolic, antioxidant, and antiglycative dysfunctions [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 87%
“…So far, fCCM has been associated with loss-of-function mutations in three genes, KRIT1 / CCM1 , CCM2 and PDCD10 / CCM3 , which have been implicated in a plethora of essential physiological functions, including modulation of cadherin- and integrin-mediated cell adhesion, actin cytoskeleton dynamics, and signal transduction involved in the maintenance of endothelial barrier stability [ 7 ]. However, no mutation in these CCM genes were found in up to 15% of fCCM cases, suggesting the potential existence of additional causative determinants [ 8 , 9 ]. Conversely, mutations in the three known CCM genes were rarely detected in sCCM lesions, which instead resulted associated mainly with somatic mutations in other genes [ 10 , 11 , 12 ], suggesting that fCCM and sCCM lesions may have a distinct genetic origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large deletions have been reported for all three CCM genes [ 2 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Their size ranges from a few hundred kilobases to 1.9 megabases [ 24 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides KRIT1 (also known as CCM1), whose mutations account for more than 50% of fCCM cases, CCM disease has been associated with mutations in two other genes, CCM2 and PDCD10 (also known as CCM3), which account for about 20% and 10% of the cases, respectively [ 9 ]. However, accumulated evidence in endothelial-specific conditional knockout (cKO) mouse models has clearly demonstrated that even the homozygous loss of any of the three known CCM genes is not sufficient to cause the formation of CCM lesions, thus confirming the necessary contribution of additional determinants, including microenvironmental risk factors and genetic modifiers of tissue sensitivity to stressful conditions [ 8 , 10 , 11 ]. Accordingly, over the last decade, it has clearly emerged that KRIT1 loss-of-function predisposes the development of CCM lesions by exerting pleiotropic effects on key redox-sensitive mechanisms involved in cellular homeostasis and defenses against oxidative stress and inflammation, leading to enhanced endothelial cell susceptibility to oxy-inflammatory insults [ 8 , 10 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%